The Effect of Iodine Teat Dipping on Subclinical Mastitis, Milk Deterioration, and Total Bacterial Count in Fresh Cow Milk in Sumbang Sub-district, Banyumas - Valiana, Ana; Ifani, Merryafinola; Subagyo, Yusuf (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aimed to evaluate the effect of post-milking teat dipping using a 1% iodine solution on subclinical mastitis incidence, milk spoilage, and total microbial count in lactating dairy cows. The research was conducted in Limpakuwus and Susukan Villages, Sumbang Sub-district, Banyumas Regency, selected through purposive sampling. The study involved dairy farmers from the PESAT Cooperative who agreed to implement teat dipping procedures. Fresh milk samples were collected from 21 lactating dairy cows. Data were analyzed using paired t-tests and presented descriptively in tables. The results showed a significant decrease in subclinical mastitis, milk spoilage, and total bacterial count following the teat dipping treatment. Statistical analysis indicated a highly significant effect (P<0.01) between teat dipping and the reduction in subclinical mastitis based on California Mastitis Test (CMT) results, with a 56.25% decrease in incidence. Significant effects (P<0.05) were also observed between teat dipping and milk spoilage, as well as total bacterial count. The number of alcohol test-positive samples declined by 62.5% (from 8 to 3 cows), while negative samples increased by 38.5% (from 13 to 18 cows). The average total bacterial count in fresh milk decreased by 49.59%. These findings suggest that teat dipping with a 1% iodine solution is an effective hygiene practice that should be integrated into the milking management routine of dairy farmers in Sumbang Sub-district to reduce subclinical mastitis, milk spoilage, and microbial contamination.